Beyond the brain: disrupted in schizophrenia 1 regulates pancreatic β‐cell function via glycogen synthase kinase‐3β. Issue 2 (6th November 2015) - Jurczyk, Agata; Nowosielska, Anetta; Przewozniak, Natalia; Aryee, Ken‐Edwin; Dilorio, Philip; Blodgett, David; Yang, Chaoxing; Campbell‐Thompson, Martha; Atkinson, Mark; Shultz, Leonard; Rittenhouse, Ann; Harlan, David; et al.
Abstract : Individuals with schizophrenia and their first‐degree relatives have higher rates of type 2 diabetes (T2D) than the general population (18–30 vs. 1.2–6.3%), independent of body mass index and antipsychotic medication, suggesting shared genetic components may contribute to both diseases. The cause of this association remains unknown. Mutations in disrupted in schizophrenia 1 ( DISC1 ) increase the risk of developing psychiatric disorders [logarithm (base 10) of odds = 7.1]. Here, we identified DISC1 as a major player controlling pancreatic β‐cell proliferation and insulin secretion via regulation of glycogen synthase kinase‐3β (GSK3β). DISC1 expression was enriched in developing mouse and human pancreas and adult β‐ and ductal cells. Loss of DISC1 function, through siRNA‐mediated depletion or expression of a dominant‐negative truncation that models the chromosomal translocation of human DISC1 in schizophrenia, resulted in decreased β‐cell proliferation (3 vs. 1%; P < 0.01), increased apoptosis (0.1 vs. 0.6%; P < 0.01), and glucose intolerance in transgenic mice. Insulin secretion was reduced (0.5 vs. 0.1 ng/ml; P < 0.05), and critical β‐cell transcription factors Pdx1 and Nkx6.1 were significantly decreased. Impaired DISC1 allowed inappropriate activation of GSK3β in β cells, and antagonizing GSK3β (SB216763; IC50 = 34.3 nM) rescued the β‐cell defects. These results uncover an unexpected role for DISC1 in normal β‐cell physiology and suggest that DISC1 dysregulation contributes to T2D independently of its importance for cognition.—Jurczyk, A., Nowosielska, A., Przewozniak, N., Aryee, K.‐E., DiIorio, P., Blodgett, D., Yang, C., Campbell‐Thompson, M., Atkinson, M., Shultz, L., Rittenhouse, A., Harlan, D., Greiner, D., Bortell, R. Beyond the brain: disrupted in schizophrenia 1 regulates pancreatic β‐cell function via glycogen synthase kinase‐3β. FASEB J. 30, 983–993 (2016). www.fasebj.org